Anisotropic Expansion of an M2L4 Coordination Capsule: Host Capability and Frame Rearrangement. Issue 11 (10th February 2015) - Yamashina, Masahiro; Yuki, Tsubasa; Sei, Yoshihisa; Akita, Munetaka; Yoshizawa, Michito
Abstract Anisotropic expansion of a spherical M2L4 coordination capsule through the elongation of the ligand led to a new M2L′4 capsule. The expanded capsule provides an elliptical cavity encircled by polyaromatic frameworks with large openings and thereby can encapsulate elliptical fullerene C70 and monofunctionalized fullerene C60 in high yields. In addition, selective formation of a new M2L2L′2 capsule occurs by mixing the original M2L4 and expanded M2L′4 capsules in a 1:1 ratio upon addition of C60 or monofunctionalized C60 as a template molecule.